Cephalometric appraisal of the hyoid triangle in brazilian people of Piracicaba's region - Maria Julia Pereira Coelho Ferraz; Darcy Flávio Nouer; Fausto Bérzin; Meire Alves Sousa; Fábio Romano (Universidade Estadual de Campinas, 2015)
The Triangle Hyoid was measured by cephalometric measures in Brazilian individuals from Piracicaba's region by establishing comparisons with the values existing in the literature objectiving to establish values of normality for the position of the hyoid bone. The sample consisted of 31 cephalometric radiographs of Brazilian individuals with Angle's Class I malocclusion, mix dentition,16 boys and 15 girls with ages raging from 8 to 15 years. The gotten data had submitted it test "t" of Student that showed the occurrence of sexual dimorfism for the ântero-posterior position of the hyoid bone(H) to the retrognation (RGn). The antero-posterior hyoid position (H) in relation to the third cervical vertebra (C3) was constant, with values of 34.03 mm and standard deviation of 3.85. The distances between antero-posterior position of C3 and symphysis (RGn) were similar to those found in the literature. The vertical position of the hyoid bone was higher and less inclined. The correlation coefficient between the atlas vertebrae to posterior nasal espine (AA-PNS) and C3-H was significant (0.56), which is suggesting that the hyoid bone represents the previous limit of the upper airspace in a level more inferior than the PNS in accordance with the literature. It concluded itself that there is a related sexual differences and face standard with the position of the hyoid bone indicates the necessity of a refined evaluation of this bone, therefore represents an important element for the orthodontic and functional orthopedic and speech therapist and physitherapist.